Working Paper 28: Regulating cryptocurrencies: challenges and considerations (Basel Institute on Governance Working Papers, 2019)
Cryptocurrency regulations are developing fast. Across the world, authorities are reacting to the emerging threat posed by criminals using new payment methods to conceal and launder the proceeds of their crimes.However, as the application of anti-money laundering/combating the financing of terrorism (AML/CFT) due diligence requirements becomes stricter and more entities implement preventative measures, criminals are constantly looking elsewhere for potential havens for their illicit activities.This Working Paper offers an insight into some potential consequences of changes in AML/CFT legislation in relation to cryptocurrency exchange services and virtual assets.
Keywords: cryptocurrencies; virtual assets; virtual assets-based money laundering; AML/CFT; anti-money laundering; FinTech